Observasi Metode Pembelajaran PPKN Di SMP Negeri 35 Medan - Joy Novi Yanti Lumbantobing; Jojor Mindo Manullang; Murniwati Lase; Al Firman; Reylan Silverius Sinaga (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This article is entitled "Observation of PPKn Learning Methods at SMP Negeri 35 Medan". This article aims to find out the difficulties or problems faced by teachers in PPKn learning at SMP Negeri 35 Medan and look for methods or strategies that can be used to overcome these problems. The research method used is descriptive qualitative with data collection techniques through observation, interviews, literature study and documentation. Difficulties faced by teachers in learning include lack of facilities, differences in student backgrounds, lack of student interest and motivation, as well as lack of parental guidance and lack of economic support for students' families. Solutions implemented by teachers include a closer approach, special attention, additional lesson hours, and home tutoring. This article also provides suggestions for improvement and further research.